Studi Kajian: Konvergensi IFRS, PSAK, Undang-Undang Perpajakan dan Dampaknya terhadap Aset Tetap - Dewi Pudji Rahayu (Journal of Accounting and Investment, 2015)
The Revised Statement of Financial Accounting Standard for Property, Plant, and Equipment (PSAK 16) has been fully adopted from International Accounting Standard 16 on January 2008. Development of national standards that harmonize PSAK and IFRS have some advantages in the aspects of costs reduction in preparing financial statements. This research was based on literature review of several studies. The objectives of this research are to explore general difference among IFRS, PSAK, and tax regulatory particularly on Property, Plant and Equipment using cost methode (depreciation) and revaluation simulations, and Indonesia readiness to fully adopt IFRS in ASEAN region. The result of this research showed that using cost method and revaluation for simulation had no significant difference toward tax expense paid by tax payers due to this difference would be eliminated by deffered tax for next month. Indonesia should revise tax regulatory and adopt IFRS in it because this can make internasional  investors analize Financial Report easily.